Unexpected Steve Observations at High Latitude During Quiet Geomagnetic Conditions - Pinto-Abarzua, V (John Wiley and Sons Inc, 2024)
Strong Thermal Emission Velocity Enhancement (STEVE), is a captivating optical phenomenon typically observed in the mid-latitude ionosphere. This paper presents an intriguing observation of a STEVE event at high-latitudes, approximately 10 degrees poleward of previously documented observations. This event was recorded in Yellowknife, Canada, by a TREx RGB imager and a citizen scientist. Swarm satellites traversed the latitude of the observation, measuring extreme westwards ion drift velocities exceeding 4 km/s. Such velocities are more typically associated with the subauroral region located at mid-latitudes, rather than at the high-latitudes reported here. Significantly, this event occurred without a substorm, which differs from previous STEVE observations. While high-latitude radars detected fast ionospheric equatorward flows, GOES satellite did not record any injections. These observations suggest that the inner magnetosphere is highly inflated. This unique case study raises new questions surrounding subauroral dynamics and the influence of magnetospheric configurations on ionospheric responses. © 2024. The Author(s).
Keywords: STEVE; SAID; subauroral science; storm; substorm; quiet-time